Giving Birth with Rape in One's Past: A Qualitative Study. Issue 3 (18th September 2013) - Halvorsen, Lotta; Nerum, Hilde; Øian, Pål; Sørlie, Tore
Abstract Background Rape is one of the most traumatizing violations a woman can be subjected to, and leads to extensive health problems, predominantly psychological ones. A large proportion of women develop a form of posttraumatic stress termed Rape Trauma Syndrome. A previous study by our research group has shown that women with a history of rape far more often had an operative delivery in their first birth and those who gave birth vaginally had second stages twice as long as women with no history of sexual assault. The aim of this study is to examine and illuminate how women previously subjected to rape experience giving birth for the first time and their advice on the kind of birth care they regard as good for women with a history of rape. Methods A semi‐structured interview with 10 women, who had been exposed to rape before their first childbirth. Data on the birth experience were analyzed by qualitative content analysis. Results The main theme was "being back in the rape" with two categories: "reactivation of the rape during labor, " with subcategories "struggle, " "surrender, " and "escape" and "re‐traumatization after birth, " with the subcategories "objectified, " "dirtied, " and "alienated body." Conclusion A rape trauma can be reactivated during the first childbirth regardless of mode of delivery. After birth, the women found themselves re‐traumatized with the feeling of being dirtied, alienated, and reduced to just a body that another body is to come out of. Birth attendants should acknowledge that the common measures and procedures used during normal birth or cesarean section can contribute to a reactivation of the rape trauma.